2005
DOI: 10.1523/jneurosci.1445-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Depression in Thalamocortical Synapses of Cat Primary Visual Cortex

Abstract: Neurons in primary visual cortex exhibit several nonlinearities in their responses to visual stimuli, including response decrements to repeated stimuli, contrast-dependent phase advance, contrast saturation, and cross-orientation suppression. Thalamocortical synaptic depression has been implicated in these phenomena but has not been examined directly in visual cortex in vivo. We assessed depression of visual thalamocortical synapses in vivo using 20 -100 Hz trains of electrical stimuli delivered to the LGN. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
154
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(168 citation statements)
references
References 71 publications
13
154
1
Order By: Relevance
“…Our most recent estimates indicate that there are only an average of between 100 and 300 thalamic synapses per SS cell (Peters and Payne, 1993;Ahmed et al, 1994;Anderson et al, 1994;Binzegger et al, 2004). This contrasts with the rat barrel cortex, where the thalamic axons (Boudreau and Ferster, 2005;Banitt et al, 2007) are estimated to form ϳ600 synapses with their targets (Bruno and Sakmann, 2006; but see Meyer et al, 2010).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our most recent estimates indicate that there are only an average of between 100 and 300 thalamic synapses per SS cell (Peters and Payne, 1993;Ahmed et al, 1994;Anderson et al, 1994;Binzegger et al, 2004). This contrasts with the rat barrel cortex, where the thalamic axons (Boudreau and Ferster, 2005;Banitt et al, 2007) are estimated to form ϳ600 synapses with their targets (Bruno and Sakmann, 2006; but see Meyer et al, 2010).…”
Section: Introductionmentioning
confidence: 78%
“…The excitatory input to spiny stellate (SS) cells is dominated by the input from layer 6 pyramids and other layer 4 pyramids (Ahmed et al, 1994;Binzegger et al, 2004). Even though activation of single dLGN afferents in vitro evokes twofold larger EPSPs than the other known inputs to the layer 4 SS cells (Stratford et al, 1996;TarczyHornoch et al, 1999), the thalamocortical synapses undergo short-term depression that offsets this advantage in vivo (Boudreau and Ferster, 2005;Banitt et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is ubiquitous in vertebrate neural circuits (Boudreau and Ferster 2005) and may thus contribute to directional selectivity and other spatiotemporal computations across sensory modalities and species.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Freeman et al (2002) proposed that synaptic depression in thalamocortical synapses might underlie crossorientation suppression (but see Boudreau and Ferster, 2005). Based on their recordings in cat area 17, they suggest that a cortical basis is unlikely because the suppression is essentially immune to visual adaptation and is engaged by gratings drifting faster than 20 Hz, which exceeds the temporal resolution of most cells in primary visual cortex.…”
Section: Discussionmentioning
confidence: 99%
“…The time constant for recovery from synaptic depression in vitro is reported to be from 60 to 600 ms Thomson and Deuchars, 1997;Varela et al, 1997), whereas we observed recovery from suppression no more than 20 ms after response onset. Furthermore, Boudreau and Ferster (2005) studied synaptic depression at the thalamocortical synapse in anesthetized cats and concluded that synaptic depression is near saturation at spontaneous levels of activity. These findings that indicate synaptic depression is an unlikely source for cross-orientation suppression.…”
Section: Discussionmentioning
confidence: 99%